Penerapan Model Group Investigation Bantuan Alat Peraga untuk Meningkatkan Minat dan Hasil Belajar Matematika Peserta Didik - Thoriqatul Amamy; Agusfianuddin; Pujilestari; Zainal Abidin (Jurnal Kependidikan Ki Hajar Dewantara, 2026)
The low level of students’ interest and mathematics learning outcomes in solid geometry indicates the need for an instructional approach that actively engages students while helping them visualize abstract mathematical concepts. This study aimed to describe the implementation of the Group Investigation learning model assisted by bamboo-stick manipulatives to improve the learning interest and mathematics achievement of eighth-grade students at MTs NW Senyiur. This study employed classroom action research based on the Kemmis and McTaggart model and was conducted in two cycles. Each cycle consisted of planning, action, observation, and reflection stages and was implemented in two meetings. The research participants comprised 22 students, although only 21 students completed the learning evaluation. Data were collected using a learning-interest questionnaire, observation sheets of teacher and student activities, and mathematics achievement tests. The data were analyzed descriptively using percentages of learning interest, classroom activities, and classical learning mastery. The findings showed that the average percentage of students’ learning interest increased from 64.77% in Cycle I, categorized as moderate, to 78.86% in Cycle II, categorized as good. Classical learning mastery increased from 42.85% in Cycle I to 80.95% in Cycle II. Students’ learning activities also improved from 65.83% to 85.83%. These findings indicate that the Group Investigation learning model assisted by bamboo-stick manipulatives created a more active, collaborative, and concrete learning environment, thereby improving students’ interest and mathematics learning outcomes in the topics of cubes and rectangular prisms.